Interactions between small rodents and their food plants in tundra habitats - Soininen, Eeva Marjatta (Universitetet i Tromsø, 2012)
Papers 2, 3, 4 and 5 are not available in Munin: 2. Soininen E.M., Zinger L., Gielly L., Bellemain, E., Br athen, K.A., Brochmann, C., Epp, L.S., Gussarova, G., Hassel, K., Henden, J.-A., Killengreen, S.T., R am a, T., Sten ien, H.K., Yoccoz, N.G. and Ims, R.A.: 'Shedding new light on the diet of Norwegian lemmings : metabarcoding of stomach DNA' (manuscript) 3. Soininen E.M., Ravolainen V.T., Br athen K.A., Yoccoz N.G., Gielly, L. and Ims R.A.: 'Arctic small rodents have diverse diets and exible food preferences' (manuscript) 4. Soininen E.M., Ehrich D., Lecomte N., Yoccoz N.G., Tarroux A., Berteaux D., Gauthier G., Gielly L. and Ims R.A.: 'Sources of variation in small rodent trophic niche : new insights from DNA metabarcoding and stable isotope analysis' (manuscript) 5. Soininen E.M., Br athen, K.A., Jusdado J.G.H, Reidinger S., Hartley S.E.: 'More than herbivory : levels of silica-based plant defences in grasses varies with genotype, species and location', Oikos (2012), Online before print. Available at http://dx.doi.org/10.1111/j.1600-0706.2012.20689.x Small rodents are key herbivores of arctic ecosystems, where their cyclic population dynamics have important implications for vegetation dynamics. The role of vegetation for shaping small rodent population dynamics remains, however, unclear. Evaluation of this interaction has been greatly hampered by the rather fragmentary knowledge of small rodents feeding ecology, which in turn is due to methodological challenges in studying small rodent diets. In this thesis, I investigated interactions between small rodents and vegetation, focusing on variability of both diets and plant defences induced by rodent herbivory. In order to overcome limitations set by methods, I have evaluated the use of two recently developed methods and one traditionally used method for studying small rodent diets. I found that novel DNA metabarcoding methods give the best taxonomic resolution whereas traditional microhistological methods may still be useful to elucidate which plant parts ...